584. PREVALENCE AND SURGICAL TREATMENT OF TRUE SHORT ESOPHAGUS IN GERD AND HIATUS HERNIA. (24th September 2022) - Lugaresi, Marialuisa; Tassi, Valentina; Daddi, Niccolò; Bassi, Francesco; Pilotti, Vladimiro; Mattioli, Sandro
Abstract: Prevalence and surgical treatment of true short esophagus (TSE), defined as the intra operative position of the apex of the gastric folds (endoscopic cardia- EC) <1.5 cm below the apex of the diaphragmatic hiatus after extend isolation of lower esophagus, are controversial. We report on 441 patients affected by GERD/HH, consecutively operated upon with three different minimally invasive surgical techniques, successively regularly followed up according to protocol, in the period 2004-2022. The distance between the endoscopically-localized EC marked with clips by the surgeon and the apex of the diaphragmatic hiatus after maximal thoracic esophagus mobilization was measured during the laparoscopic procedure. A standard Nissen fundoplication (SN) was performed in cases with an abdominal length >1.5 cm; in cases of TSE a laparoscopic-thoracoscopic Collis-Nissen (CN) or laparoscopic Stomach Around Stomach Fundoplication (SASF) in elderly patients was performed. The fundoplication superior margin was always fixed below the hiatus, over the EC. Patients' symptoms, radiological and endoscopic data were pre/postoperatively recorded. After intra-thoracic esophageal mobilization (median =9 cm), TSE was diagnosed in 30.38 % of 441 cases (31, 8% in 311/2004-2017; 27, 7% in 130/2017-2022). SN was performed in 69%, CN in 23% and SASF in 7%. On 441 cases regularly followed up with a median of 106 months, HH relapse was radiologically diagnosed in 3%, with excellent, good, fair, and poor outcomes respectively in 46.3%, 43.2%, 6.7%, and 3.8% of cases. No outcome significant differences among SN CN and SASF, were recorded. In the period 2004-2022, prevalence of TSE was constant in a significant third of patients routinely submitted to GERD/HH surgery. In the presence of TSE, CN and SASF performed according to determined surgical principles may achieve results as satisfactory as those obtained with SN.